A pilot study optimizing metabolomic and lipidomic acquisition in serum for biomarker discovery in nonalcoholic fatty liver disease - He, Dandan; Su, Yang; Meng, Duanyue; Wang, Xinmiao; Wang, Jun; Ye, Hui (Journal of mass spectrometry and advances in the clinical lab, 2021)
•The metabolomic workflow for disease biomarker discovery was optimized.•Two separation modes using T3 and amide columns and two polarity modes were used.•Metabolome and lipidome coverage was improved via an integrative workflow.•Increased lysophosphatidylcholines, diacylglycerols and acylcarnitines were noted in sera of NAFLD patients. The worldwide prevalence of non-alcoholic fatty liver disease (NAFLD) has stimulated work to identify biomarkers and develop effective treatments. Metabolomics is an emerging tool that has been widely applied to discover biomarkers and simultaneously uncover pathological mechanisms. Here, we aim to optimize metabolomic acquisition with the goal of obtaining a systemic metabolic profile to unravel the potential link between dysregulated metabolism and NAFLD. We analyzed serum samples collected from healthy subjects (n = 8) and NAFLD patients (n = 8) via an integrative analytical workflow using two orthogonal separation modes with T3 and amide columns and two ionization polarity modes on a UPLC-ESI-Q/TOF. Data dependent acquisition was employed for data acquisition. Differentially expressed metabolites and lipids were identified by comparing the collected metabolic and lipidomic profiles between the healthy subjects and NAFLD patients. The integrative LC-MS/MS analytical workflow employed here features an improved coverage of metabolites and lipids, which leads to the identification of 20 potential biomarkers of NAFLD, including lipids, acylcarnitines, and organic acids. This pilot study has identified potential biomarkers for NAFLD and revealed corresponding dysregulated metabolic pathways related to NAFLD's occurrence and progression, establishing a molecular basis for NAFLD diagnosis and therapeutic intervention.